Harmonized system of quality assessment for electronic components. Fixed resistors for use in electronic equipment. Blank detail specification: fixed resistor networks in which not all resistors are individually measurable. Assessment level E Part 05.01, (15th September 1985) - British Standards Institution,
No abstract available